2015
DOI: 10.1001/jamaneurol.2014.3613
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cerebrospinal Fluid Levels of Lateral Olfactory Tract Usher Substance (LOTUS) With Disease Activity in Multiple Sclerosis

Abstract: IMPORTANCE Although multiple sclerosis (MS) is generally considered an autoimmunedemyelinating disorder of the central nervous system, axonal degeneration through Nogo receptor-1 signaling was recently recognized as an important pathological feature. Our previous identification of lateral olfactory tract usher substance (LOTUS), an endogenous Nogo receptor-1 antagonist, prompted us to analyze the relationship between LOTUS levels of cerebrospinal fluid and the clinical course of MS to evaluate whether LOTUS co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…In addition to our previous findings regarding LOTUS function in mice, proteomic studies also suggested that LOTUS is present in human CSF . Using a biochemical approach, we successfully detected LOTUS in human CSF, and clarified the relationship between LOTUS levels in the CSF and clinical course or disease activity in MS …”
Section: Potential Application Of Lotus As a Biomarker Of Mssupporting
confidence: 54%
See 1 more Smart Citation
“…In addition to our previous findings regarding LOTUS function in mice, proteomic studies also suggested that LOTUS is present in human CSF . Using a biochemical approach, we successfully detected LOTUS in human CSF, and clarified the relationship between LOTUS levels in the CSF and clinical course or disease activity in MS …”
Section: Potential Application Of Lotus As a Biomarker Of Mssupporting
confidence: 54%
“…[3][4][5] In addition to our previous findings regarding LOTUS function in mice, proteomic studies also suggested that LOTUS is present in human CSF. 38 Using a biochemical approach, we successfully detected LOTUS in human CSF, and clarified the relationship between LOTUS levels in the CSF and clinical course or disease activity in MS. 39 In our analysis of CSF LOTUS levels, we initially divided the MS patients into RRMS and SPMS groups; those in the former group were classified into the relapse and remission groups according to findings of gadolinium-enhanced MRI lesions, medical history and clinical findings. LOTUS concentration was measured by quantitative immunoblotting.…”
Section: Potential Application Of Lotus As a Biomarker Of Msmentioning
confidence: 99%
“…Indeed, regenerating axons after SCI in LOTUS-TG mice overexpressed LOTUS; thus, the maintenance of LOTUS expression may be important for overcoming the influence of AGIs. However, the LOTUS concentration in cerebrospinal fluid (CSF) is markedly decreased in patients with cerebral infarction (unpublished data) and multiple sclerosis 29 compared with normal healthy controls. This phenomenon suggests that LOTUS expression in the CNS or secretion into the CSF is down-regulated by CNS damage and/or inflammation, although how LOTUS expression or secretion is down-regulated remains unknown.…”
Section: Discussionmentioning
confidence: 96%
“…The maintenance or increase of LOTUS expression might be important in order to overcome the influence of AGIs. In humans, in patients with cerebral infarction (Takahashi K, Tanaka F, Takei K, 2019), multiple sclerosis, and meningitis, the LOTUS concentration in the cerebrospinal fluid (CSF) significantly decreases compared with healthy people, indicating that LOTUS expression in the CNS or secretion into the CSF is downregulated by CNS damage and/or inflammation. However, how LOTUS expression or secretion decreases is still not determined.…”
Section: A Novel Strategy Of Neuronal Regeneration Using Physiologicamentioning
confidence: 99%